(untitled) (Jurnal Ekonomi Pembangunan Widya Mandira, 2026)
This study aims to analyze the effect of the Labor Force Participation Rate, Human Development Index, and Population Growth Rate on the Poverty Rate of regencies/cities in East Nusa Tenggara Province. The study uses an associative quantitative approach with secondary data obtained from official publications of the Central Statistics Agency. The data analysis technique employs multiple linear regression through simultaneous and partial tests. The results show that the Labor Force Participation Rate, Human Development Index, and Population Growth Rate simultaneously have a significant effect on the Poverty Rate. Partially, only the Population Growth Rate has a negative and significant effect, while the Labor Force Participation Rate and Human Development Index do not have a significant effect. These findings indicate that poverty in East Nusa Tenggara is multidimensional and is not only determined by labor participation or human development achievements, but also by population dynamics and the region’s ability to manage its population potential. Therefore, poverty alleviation policies need to be directed toward creating decent jobs, increasing labor productivity, equalizing basic services, and managing population growth as a foundation for regional development